Autophagy-Mediated Inflammatory Cytokine Secretion in Sporadic ALS Patient iPSC-Derived Astrocytes. (22nd August 2022) - BaofengFeng,; Amponsah, Asiamah Ernest; Guo, Ruiyun; Liu, Xin; Zhang, Jinyu; Du, Xiaofeng; Zhou, Zijing; He, Jingjing; Ma, Jun; Cui, Huixian
Abstract : Background . Astrocytes can be involved in motor neuron toxicity in amyotrophic lateral sclerosis (ALS) induced by noncell autonomous effects, and inflammatory cytokines may play the main role in mediating this process. However, the etiology of aberrant cytokine secretion is unclear. The present study assessed possible involvement of the mTOR-autophagy pathway in aberrant cytokine secretion by ALS patient iPSC-derived astrocytes. Method and Results . PBMCs from sporadic ALS patients and control subjects were reprogrammed into iPSCs, which were then differentiated into astrocytes and/or motor neurons. Comparison with control astrocytes indicated that conditioned medium of ALS astrocytes reduced the viability of the control motor neurons (p < 0.05 ) assessed using the MTT assay. The results of ELISA showed that the concentrations of TNF α, IL1 β, and IL6 in cell culture medium of ALS astrocytes were increased (p < 0.05 ). ALS astrocytes had higher p62 and mTOR levels and lower LC3BII/LC3BI ratio and ULK1 and p-Beclin-1 (Ser15) levels (p < 0.05 ), indicating defective autophagy. Exogenous inhibition of the mTOR-autophagy pathway, but not the activation of the pathway in control subject astrocytes, increased the levels of p62 and mTOR and concentration of IL-1 β, TNF- α, and IL-6 in cell culture medium and decreased the LC3BII/LC3BI ratio and levels of ULK1 and p-Beclin-1 (Ser15), and these changes were comparable to those in ALS astrocytes. After 48 h of rapamycin (autophagy activator) and 3-methyladenine (autophagy inhibitor) treatments, the exogenous activation of the mTOR-autophagy pathway, but not inhibition of the pathway, in ALS astrocytes significantly reduced the concentrations of TNF α, IL1 β, and IL6 in cell culture medium and reduced the levels of p62, while increasing the levels of LC3B-II/LC3B-I, ULK1, and p-Beclin-1 (Ser15), and these changes were comparable to those in control subject astrocytes. Conclusion . Alteration in the mTOR/ULK1/Beclin-1 pathway regulated cytokine secretion in ALS astrocytes, which was able to lead to noncell autonomous toxicity. Autophagy activation mitigated cytokine secretion by ALS astrocytes.